Searching Behaviour of Metaphycus helvolus, (Compere) and Scutellista cyanea, Motschulsky on Hemispherical Scale, S. coffeae (Walker) - Ibrahim, Abdul Ghani (1988)
The host searching of Metaphycus helvolus and Scutellisa cyanea were studied under two different constant temperatures of18 °Cand 26 °C. In the course of host-searching, both parasitoids were involved with host-drilling, handling, preening, walking and resting. Host-feeding only occurred with M. helvolus. S. cyanea spent more than fifty percent of the time walking at both temperatures. However, M. helvolus spent a greater proportion of time for three activities: walking, host-drilling and preening. The amount of time spent by M. helvolus on host-feeding was less than ten percent. The areas covered by M. helvolus and S. cyanea for host-searching at 26°C were 933 mm2/hr and 3517 mm2/hr. respectively.